Semi-Mechanistic Modeling of HY-021068 Based on Irreversible Inhibition of Thromboxane Synthetase - Li, Ping; Huang, Jie; Geng, Donghao; Liu, Peihua; Chu, Zhaoxing; Zou, Jianjun; Yang, Guoping; Liu, Li (Frontiers in Pharmacology, 2020)
Background: HY-021068 (4-(2-(1H-imidazol-1-yl) ethoxy)-3-methoxybenzoate), developed by Hefei Industrial Pharmaceutical Institute Co., Ltd (Anhui, China), is a potential thromboxane synthetase inhibitor under development as an anti-platelet agent for the treatment of stroke. A semi-mechanistic pharmacokinetic/pharmacodynamic (PK/PD) model was developed to characterize the PK of HY-021068 and its platelet aggregation inhibitory effect in beagle dogs. Method: Beagle dogs received single oral administration of 2.5 mg/kg HY-021068 or consecutively oral administration of 5 mg/kg HY-021068 once daily for 7 days. The plasma concentration of HY-021068 and the platelet aggregation rate were determined by LC-MS/MS assay and a photometric method, respectively. The PK/PD data was sequentially fitted by Phoenix NLME. The PK/PD parameters of HY-021068 in beagle dogs were estimated by 2.5 mg/kg and 5 mg/kg dosing on the 1st day, and then used to simulate the platelet aggregation rate of HY-021068 on the 7th day after 5 mg/kg dosing daily. Result: A one-compartment model with saturable Michaelis-Menten elimination was best fitted to the PK of HY-021068. A mechanistic PD model based on irreversible inhibition of thromboxane synthetase was constructed to describe the relationship between plasma concentration of HY-021068 and platelet aggregation rate. Diagnostic plots showed no obvious bias. Visual predictive check confirmed the stability and reliability of the model. Most of PK/PD observed data on the 7th day after 5 mg/kg dosing fell in the 90% prediction interval. Conclusions: We established a semi-mechanistic PK/PD model for characterizing the PK of HY-021068 and its anti-platelet effect in beagle dogs. The model can be used to predict the concentration and platelet aggregation rate under different dosage regimen of HY-021068, and might be served as a reference for dose design in the future clinical studies.